The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ange.201904808
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Columnar Triazole Quartets: An Example of Synergistic Hydrogen‐Bonding/Anion–π Interactions

Abstract: The self-assembly of triazole amphiphiles was examined in solution, the solid state,and in bilayer membranes. Single-crystal X-ray diffraction experiments show that stacked protonated triazole quartets (T 4 )a re stabilized by multiple strong interactions with two anions.H ydrogen bonding/ion pairing of the anions are combined with anion-p recognition to produce columnar architectures.I nb ilayer membranes,l ow transport activity is observed when the T 4 channels are operated as H + /X À translocators,b ut hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…A series of experiments were performed by using an H + selective carrier (FCCP) or a K + -selective carrier (valinomycin). There was no significant difference in the transport activity, confirming that these artificial triazole channels have no cation selectivity ( Figure 21 ) [ 63 ].…”
Section: Artificial Proton Channelsmentioning
confidence: 79%
See 3 more Smart Citations
“…A series of experiments were performed by using an H + selective carrier (FCCP) or a K + -selective carrier (valinomycin). There was no significant difference in the transport activity, confirming that these artificial triazole channels have no cation selectivity ( Figure 21 ) [ 63 ].…”
Section: Artificial Proton Channelsmentioning
confidence: 79%
“…A selective anion recognition has to be combined with fast anion translocation along the directional pathways in channels. A series of protonated amino-triazole amphiphiles were synthesized and characterized by Barboiu et al to form self-assembled channels of stacked triazole quartets ( Figure 20 ) [ 63 ].…”
Section: Artificial Proton Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5] Barboiu et al reported self-assembled columnar triazole quartets as artificial channels in lipid vesicles. 6 However, it remains to be seen whether successful self-assembly and chloride transport can be achieved under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%